Role of Wnt Signaling in Adult Hippocampal Neurogenesis in Health and Disease - Arredondo, Sebastian B.; Valenzuela-Bezanilla, Daniela; Mardones, Muriel D.; Varela-Nallar, Lorena (Frontiers in Cell and Developmental Biology, 2020)
Neurogenesis persists during adulthood in the dentate gyrus of the hippocampus. Signals provided by the local hippocampal microenvironment support neural stem cell proliferation, differentiation, and maturation of newborn neurons into functional dentate granule cells, that integrate into the neural circuit and contribute to hippocampal function. Increasing evidence indicates that Wnt signaling regulates multiple aspects of adult hippocampal neurogenesis. Wnt ligands bind to Frizzled receptors and co-receptors to activate the canonical Wnt/β-catenin signaling pathway, or the non-canonical β-catenin-independent signaling cascades Wnt/Ca2+ and Wnt/planar cell polarity. Here, we summarize current knowledge on the roles of Wnt signaling components including ligands, receptors/co-receptors and soluble modulators in adult hippocampal neurogenesis. Also, we review the data suggesting distinctive roles for canonical and non-canonical Wnt signaling cascades in regulating different stages of neurogenesis. Finally, we discuss the evidence linking the dysfunction of Wnt signaling to the decline of neurogenesis observed in aging and Alzheimer’s disease.